Efektivitas Dan Proses Sterilisasi Uap Dalam Farmasi - Niken Rahmita; Dewi Rahmawati; Sirojul Eilma; Sari Fatul Layly; Anisya Khusnul; Dzakiya Zhihrotulwida; M. Fitrul Mubarak (CV. ITTC INDONESIA, 2025)
Sterilization is the liberation of materials or tools from various living microorganisms or their resting stages. Sterilization methods can be divided into two general groups, namely physical and chemical. Although sterilization can be achieved with certain chemicals, generally physical methods are more reliable. One of the most effective methods for killing microorganisms is using high temperatures. One of the sterilizers that uses the pressurized steam heat method is the autoclave. This review article was carried out with the aim of discussing and providing information to readers regarding the sterilization of tools and materials that will be used in medical and non-medical settings, which is very important in every manufacturing process. Apart from that, we also know the benefits and processes of sterilization that are commonly used, namely steam sterilization.